Biophysical drivers of mountain pine beetle outbreaks in lodgepole pine forests in the Intermountain West, U.S. - Jackson P. Audley; Andrew M. Latimer; Christopher J. Fettig; A. Steven Munson; Justin B. Runyon; Leif A. Mortenson; Brytten E. Steed; Kenneth E. Gibson; Carl L. Jørgensen; Stephen R. McKelvey; Joel D. McMillin; José F. Negrón (Forest Ecology and Management, 2026)

Predicting the probability of concentrated flow occurrence using a dynamic approach on high-resolution soil surface data - Sayjro K. Nouwakpo; Osama Al-Hamdan; Christopher J. Williams; Kenneth Spaeth (CATENA, 2026)

Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

Smooth Gradients or Defined Fronts: Characterizing Within-Marsh Spatial Variability of CO2 Fluxes - Lena K. Champlin; Emily Wilson; Kenneth B. Raposa; Jason S. Goldstein; Ashley Hamilton; Jason S. Krumholz; Christopher R. Peter; Megan C. Tyrrell; Jamie M. P. Vaudrey; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Multi-frequency signatures of space-leader evolution in negative cloud-to-ground lightning stepped leaders - Dylan J. Goldberg; Amitabh Nag; Kenneth L. Cummins; Mathieu N. Plaisir; Alex Tempert; A. Tyler Brower; Christopher J. Biagi; Robert G. Brown; Hamid K. Rassoul (Atmospheric Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Particulate nitrate over the Northwest Atlantic: Insights gained by comparing airborne AMS and PILS measurements - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Eva-Lou Edwards; Johnathan W. Hair; Christopher A. Hostetler; Simon Kirschler; John B. Nowak; Michael Shook; et al. (Atmospheric Environment, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Effect of water pressure on bitumen and expelled oil biomarker evolution: Insights from laboratory simulation experiments - Ahmed Khairy; Clement N. Uguna; Waleed Sh. El Diasty; Kenneth E. Peters; Christopher H. Vane; Colin E. Snape; Sherif Farouk; Will Meredith (Organic Geochemistry, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

The roles of ecology, legal structures, and threats in maintaining successful shellfish and river herring co-management in Maine - Sophia A. Chivers; Kenneth S. Cline; Christopher W. Petersen (Marine Policy, 2025)

Well-posed boundary conditions and energy stable discontinuous Galerkin spectral element method for the linearized Serre equations - Kenny Wiratama; Kenneth Duru; Stephen Roberts; Christopher Zoppou (Wave Motion, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Microbial Nitrogen Removal in South San Francisco Bay: Does It Play a Role in Eutrophication Resistance? - Kenneth M. Czapla; Michael S. Owens; Jeffrey C. Cornwell; David B. Senn; Christopher A. Francis; Ariella Chelsky (Estuaries and Coasts, 2025)
The ecosystem response to anthropogenic nitrogen (N) loading in estuarine systems is determined by hydrodynamics, biogeochemical transformation rates, and other system-specific characteristics. Historically, San Francisco (SF) Bay has been an outlier from other estuaries with an unusual resistance to eutrophication, despite having extremely high rates of nitrogen loading. Recent increases in phytoplankton biomass and an unprecedented harmful algal bloom, however, have increased the urgency to understand rates and drivers of nitrogen removal in the system. To assess benthic N cycling rates, we conducted seasonal measurements across nine sites in South and Lower South SF Bay, the two sub-embayments with the highest rates of area-normalized N loading, to determine the rates and potential drivers of denitrification and dissimilatory nitrate reduction to ammonium (DNRA). Denitrification rates averaged 60.6 ± 8.1 µmol m −2 h −1 and were primarily coupled to nitrification. Denitrification rates were positively correlated with DNRA rates and % clay. DNRA rates ranged from 0 to 20 µmol m −2 h −1 and on an annual basis averaged ~ 10% of total benthic nitrate reduction, with a negative correlation to % clay content in the surface sediment. The measured denitrification rates account for the removal of, on average, 14% of N loaded annually to South SF Bay, leaving a sizeable portion for alternate fates (e.g., recycling, export, or burial) and potential for substantial temporal and spatial variability (1–79%). This identifies the relative importance of sediment denitrification in ecosystems characterized by high nutrients and low productivity.

The effect of high pressure on hydrocarbon generation from Type-I kerogen source rocks: Implications for petroleum system evolution - Ahmed Khairy; Clement N. Uguna; Christopher H. Vane; Waleed Sh. El Diasty; Kenneth E. Peters; Colin E. Snape; Sherif Farouk; Will Meredith (International Journal of Coal Geology, 2025)

Temperature‐Related Effects on Disease Susceptibility and Immune Response in Redband Trout ( Oncorhynchus mykiss gairdneri ) Following Challenge With Flavobacterium columnare - Joshua P. Egan; Jie Ma; Veronica L. Myrsell; Zhongqi Chen; Jonathan Masingale; Christopher C. Caudill; Timothy Boyle; Julianna Browning; Shawn R. Narum; Kenneth D. Cain; Paul A. Hohenlohe (Journal of Fish Diseases, 2025)
Heat stress can increase disease risk in fishes by reducing immune function. Interactions between redband trout ( Oncorhynchus mykiss gairdneri ) and Flavobacterium columnare , a causative agent of columnaris disease, provide an opportunity to investigate the effects of temperature on immune function and disease resistance during periods of thermal stress. We conducted three trials to characterise differences in immune function and mortality between redband trout held at 18°C and 21°C following challenge with F . columnare . In trial 1, cumulative per cent mortality (CPM) was low and not statistically different between 18°C and 21°C. In trials 2 and 2, we administered higher challenge doses and observed increased CPM overall and significantly greater CPM at 21°C than 18°C. Redband trout upregulated il‐8 , tnf‐α , igm and igt following infection by F . columnare , suggesting that all of these genes may be involved in immune responses to F . columnare infection. We found no differences in the strength of the immune responses between fish held at 21°C versus 18°C. This indicated that 21°C did not elicit sufficient thermal stress to impair immune function and that increased CPM at 21°C versus 18°C was due to enhanced F . columnare virulence.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Use of electron microscopy to determine presence of coal dust in a neighborhood bordering an open-air coal terminal in Curtis Bay, Baltimore, Maryland, USA - Matthew A. Aubourg; Kenneth J.T. Livi; Gregory G. Sawtell; Carlos C. Sanchez-Gonzalez; Nicholas J. Spada; Russell R. Dickerson; Wen-An Chiou; Conchita Kamanzi; Gurumurthy Ramachandran; Ana M. Rule; Christopher D. Heaney (Science of The Total Environment, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Sport-Specific Recovery Trajectories for NCAA Collegiate Athletes Following Concussion - Spencer W. Liebel; Kathryn L. Van Pelt; Paul F. Pasquina; Thomas W. McAllister; Michael A. McCrea; Steven P. Broglio; Scott Anderson; Holly Benjamin; Thomas Buckley; Kenneth Cameron; Sara Chrisman; James Clugston; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Corrigendum: Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Impact of sorghum (Sorghum bicolor L. Moench) phenolic compounds on cancer development pathways - Aduba Collins; Abishek Bommannan Santhakumar; Nidhish Francis; Christopher Blanchard; Kenneth Chinkwo (Food Bioscience, 2024)

Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)
Ocean surface radiation measurement best practices have been developed as a first step to support the interoperability of radiation measurements across multiple ocean platforms and between land and ocean networks. This document describes the consensus by a working group of radiation measurement experts from land, ocean, and aircraft communities. The scope was limited to broadband shortwave (solar) and longwave (terrestrial infrared) surface irradiance measurements for quantification of the surface radiation budget. Best practices for spectral measurements for biological purposes like photosynthetically active radiation and ocean color are only mentioned briefly to motivate future interactions between the physical surface flux and biological radiation measurement communities. Topics discussed in these best practices include instrument selection, handling of sensors and installation, data quality monitoring, data processing, and calibration. It is recognized that platform and resource limitations may prohibit incorporating all best practices into all measurements and that spatial coverage is also an important motivator for expanding current networks. Thus, one of the key recommendations is to perform interoperability experiments that can help quantify the uncertainty of different practices and lay the groundwork for a multi-tiered global network with a mix of high-accuracy reference stations and lower-cost platforms and practices that can fill in spatial gaps.

Echocardiographic characterization of age- and sex-associated differences in cardiac function and morphometry in nonhuman primates - Maria Cristina Florio; Laura Fusini; Gloria Tamborini; Christopher Morrell; Alise McDonald; Michelle Walcott; Kenneth Ridley; Kelli L. Vaughan; Julie A. Mattison; Mauro Pepi; Edward G. Lakatta; Maurizio C. Capogrossi (GeroScience, 2024)

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Life History and Aquaculture Methods for Burbot ( Lota Lota ) - Luke P. Oliver; Christopher A. Myrick; Gary Fornshell; Kenneth D. Cain (Reviews in Fisheries Science & Aquaculture, 2024)

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

Biophotoelectrochemistry: An emerging frontier for channeling photoelectric effect into darkness zone of soils and sediments - Jie YE; Shungui ZHOU; Kenneth H. NEALSON; Christopher RENSING (Pedosphere, 2024)

Non-target effects of essential oils on selected beneficial bacteria - Ephantus J. Muturi; Kenneth M. Doll; Christopher A. Dunlap (Journal of Plant Diseases and Protection, 2024)

Real-world Retrospective Safety Analysis of OnabotulinumtoxinA for the Treatment of Patients With Concurrent Cervical Dystonia and Chronic Migraine - Christopher Rhyne; Kenneth Martinez; Juliana Stoilova; Atul Patel; Kim Becker Ifantides; Ritu Singh; Irina Yushmanova; Marjan Sadeghi; Simona Battucci; Forde Grace (Toxicon, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

Detection of the clinically persistent, pathogenic yeast spp. Candida auris from hospital and municipal wastewater in Miami-Dade County, Florida - Kristina Babler; Mark Sharkey; Sebastian Arenas; Ayaaz Amirali; Cynthia Beaver; Samuel Comerford; Kenneth Goodman; George Grills; Michelle Holung; Erin Kobetz; Jennifer Laine; Walter Lamar; et al. (Science of The Total Environment, 2023)

A census of quality-controlled Biogeochemical-Argo float measurements - Adam C. Stoer; Yuichiro Takeshita; Tanya Lea Maurer; Charlotte Begouen Demeaux; Henry C. Bittig; Emmanuel Boss; Hervé Claustre; Giorgio Dall’Olmo; Christopher Gordon; Blair John William Greenan; Kenneth S. Johnson; Emanuele Organelli; et al. (Frontiers in Marine Science, 2023)
Biogeochemical- (BGC-) Argo aims to deploy and maintain a global array of autonomous profiling floats to monitor ocean biogeochemistry. With over 250,000 profiles collected so far, the BGC-Argo network is rapidly expanding toward the target of a sustained fleet of 1,000 floats. These floats prioritize the measurement of six key properties: oxygen, nitrate, pH, chlorophyll-a, suspended particles, and downwelling light. To assess the current biogeochemical state of the ocean, its variability, and trends with confidence, it is crucial to quality control these measurements. Accordingly, BGC-Argo maintains a quality control system using manual inspection and parameter-specific algorithms for flagging and adjusting data. In this study, we provide a census of the quantity and quality of measurements from BGC-Argo based on their quality flagging system. The purpose of this census is to assess the current status of the array in terms of data quality, how data quality has changed over time, and to provide a better understanding of the quality-controlled data to current and future users. Alongside increasing profile numbers and spatial coverage, we report that for most parameters between 80 and 95% of the profiles collected so far contain high-quality BGC data, with an exception for pH. The quality of pH profiles has seen a large improvement in the last five years and is on track to match the data quality of other BGC parameters. We highlight how BGC-Argo is improving and discuss strategies to increase the quality and quantity of BGC profiles available to users. This census shows that tracking percentages of high-quality data through time is useful for monitoring float sensor technology and helpful for ensuring the long-term success of BGC-Argo.

A generic approach to construct pseudo components for oil weathering models - Xiaolong Geng; Christopher H. Barker; Amy MacFadyen; Michel C. Boufadel; Dalina L. Thrift-Viveros; Robert K. Jones; Caitlin O’Connor; Kenneth Lee (Journal of Hazardous Materials, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Effect of degradation on geotechnical behavior of glauconite sands from the U.S. Mid-Atlantic Coastal Plain - Zachary J. Westgate; Don J. DeGroot; Christopher McMullin; Yuanjing Zou; Dongdong Guo; Simon Van Haren; Ryan D. Beemer; Danilo Zeppilli; Kenneth G. Miller; James V. Browning (Ocean Engineering, 2023)

Choice of climate data influences predictions for current and future global invasion risks for two Phelsuma geckos - Nicolas Dubos; Thomas W. Fieldsend; Markus A. Roesch; Stéphane Augros; Aurélien Besnard; Arthur Choeur; Ivan Ineich; Kenneth Krysko; Boris Leroy; Sparkle L. Malone; Jean-Michel Probst; Christopher Raxworthy; et al. (Biological Invasions, 2023)
Invasion risks may be influenced either negatively or positively by climate change, depending on the species. These can be predicted with species distribution models, but projections can be strongly affected by the source of the environmental data (climate data source, Global Circulation Models GCM and Shared Socio-economic Pathways SSP). We modelled the distribution of Phelsuma grandis and P. laticauda , two Malagasy reptiles that are spreading globally. We accounted for drivers of spread and establishment using socio-economic factors (e.g., distance from ports) and two climate data sources, i.e., Climatologies at High Resolution for the Earth’s and Land Surface Areas (CHELSA) and Worldclim. We further quantified the degree of agreement in invasion risk models that utilised CHELSA and Worldclim data for current and future conditions. Most areas identified as highly exposed to invasion risks were consistently identified (e.g. in Caribbean and Pacific Islands). However, projected risks differed locally. We also found notable differences in quantitative invasion risk (3% difference in suitability scores for P. laticauda and up to 14% for P. grandis ) under current conditions. Despite both species native distributions overlapping substantially, climate change will drive opposite responses on invasion risks by 2070 (decrease for P. grandis, increase for P. laticauda ). Overall, projections of future invasion risks were the most affected by climate data source, followed by SSP. Our results highlight that assessments of current and future invasion risks are sensitive to the climate data source, especially in islands. We stress the need to account for multiple climatologies when assessing invasion risks.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Geochemical assessment and hydrocarbon potential of Oligocene–Pliocene source rocks from northeast onshore Nile Delta, Egypt - Ahmed Khairy; Waleed Sh. El Diasty; Clement N. Uguna; Kenneth E. Peters; Christopher H. Vane; Colin E. Snape; Will Meredith (International Journal of Coal Geology, 2023)

Sources and sinks of bottom water oxygen in a seasonally hypoxic fjord - Subhadeep Rakshit; Andrew W. Dale; Douglas W. Wallace; Christopher Kenneth Algar (Frontiers in Marine Science, 2023)
Deoxygenation of the ocean has been occurring over the last half century, particularly in poorly ventilated coastal waters. In coastal and estuarine environments, both the water column and sediments play key roles in controlling oxygen variability. In this study, we focus on controls of oxygen concentration in Bedford Basin (BB), a 70 m deep, seasonally hypoxic semi-enclosed fjord on the West Atlantic coast in Nova Scotia. The basin is connected to the Scotian Shelf via a narrow 20 m deep sill that restricts the resupply of bottom water. Hypoxia was recorded seasonally in 2018, 2019 and 2021 with minimum oxygen concentration of 5, 6.7 and 2.7 μM, respectively. Using a 1-D benthic-pelagic coupled model we investigate oxygen consumption and resupply processes during these years. The model was constrained with weekly water column measurements of temperature, salinity, chlorophyll-a fluorescence and dissolved oxygen from a monitoring station in the central basin together with seasonal measurements of benthic diffusive oxygen uptake. Our model suggested that 29-81%, and up to 36% of bottom water re-oxygenation occurred during the winter mixing period and through summer/fall intrusions of Scotian Shelf water, respectively. Occasional shelf water intrusions occurred rapidly, on a timescale of a few hours, and delivered equivalent amounts of oxygen as winter mixing and were sufficient to end bottom water hypoxia. Collectively, these mechanisms supplied the majority of the oxygen delivered to the bottom water. Oxygen supply to bottom waters during periods of water column stratification accounted for 19-36% of the annual flux. The mean benthic uptake was 12 ± 8 mmol m -2 d -1 and contributed ~20% of the total oxygen consumption below the sill depth. In 2021, sea surface temperature (SST) was unusually high and likely resulted in 50% less bottom water oxygenation compared to 2018 and 2019 due to increased stratification; SST in BB was found to be increasing at a rate of 0.11 ± 0.02 °C/year. Climate control on water column stratification are discussed and numerical experiments are used to compare the effects of different water column mixing scenarios on bottom water oxygenation.

Using computational fluid dynamics to develop positive-pressure precision ventilation systems for large-scale dairy houses - Seunghyeon Jung; Hanwook Chung; Mario R. Mondaca; Kenneth V. Nordlund; Christopher Y. Choi (Biosystems Engineering, 2023)

T-cell cellular stress and reticulocyte signatures, but not loss of naïve T lymphocytes, characterize severe COVID-19 in older adults - Mladen Jergović; Makiko Watanabe; Ruchika Bhat; Christopher P. Coplen; Sandip A. Sonar; Rachel Wong; Yvonne Castaneda; Lisa Davidson; Mrinalini Kala; Rachel C. Wilson; Homer L. Twigg; Kenneth Knox; et al. (GeroScience, 2023)

Empirical nitrogen and sulfur critical loads of U.S. tree species and their uncertainties with machine learning - Nathan R. Pavlovic; Shih Ying Chang; Jiaoyan Huang; Kenneth Craig; Christopher Clark; Kevin Horn; Charles T. Driscoll (Science of The Total Environment, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Time Delta Head Impact Frequency: An Analysis on Head Impact Exposure in the Lead Up to a Concussion: Findings from the NCAA-DOD Care Consortium - Jack Seifert; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Jason P. Mihalik; Larry Riggen; Stefan Duma; Alison Brooks; Kenneth L. Cameron; Christopher C. Giza; Joshua Goldman; Kevin M. Guskiewicz; et al. (Annals of Biomedical Engineering, 2022)
Sport-related concussions can result from a single high magnitude impact that generates concussive symptoms, repeated subconcussive head impacts aggregating to generate concussive symptoms, or a combined effect from the two mechanisms. The array of symptoms produced by these mechanisms may be clinically interpreted as a sport-related concussion. It was hypothesized that head impact exposure resulting in concussion is influenced by severity, total number, and frequency of subconcussive head impacts. The influence of total number and magnitude of impacts was previously explored, but frequency was investigated to a lesser degree. In this analysis, head impact frequency was investigated over a new metric called ‘time delta’, the time difference from the first recorded head impact of the day until the concussive impact. Four exposure metrics were analyzed over the time delta to determine whether frequency of head impact exposure was greater for athletes on their concussion date relative to other dates of contact participation. Those metrics included head impact frequency, head impact accrual rate, risk weighted exposure (RWE), and RWE accrual rate. Athletes experienced an elevated median number of impacts, RWE, and RWE accrual rate over the time delta on their concussion date compared to non-injury sessions. This finding suggests elevated frequency of head impact exposure on the concussion date compared to other dates that may precipitate the onset of concussion.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Quantifying spatial extents of artificial versus natural reefs in the seascape - D’amy N. Steward; Avery B. Paxton; Nathan M. Bacheler; Christina M. Schobernd; Keith Mille; Jeffrey Renchen; Zach Harrison; Jordan Byrum; Robert Martore; Cameron Brinton; Kenneth L. Riley; J. Christopher Taylor; et al. (Frontiers in Marine Science, 2022)
With increasing human uses of the ocean, existing seascapes containing natural habitats, such as biogenic reefs or plant-dominated systems, are supplemented by novel, human-made habitats ranging from artificial reefs to energy extraction infrastructure and shoreline installments. Despite the mixture of natural and artificial habitats across seascapes, the distribution and extent of these two types of structured habitats are not well understood but are necessary pieces of information for ocean planning and resource management decisions. Through a case study, we quantified the amount of seafloor in the southeastern US (SEUS; 103,220 km 2 in the Atlantic Ocean; 10 – 200 m depth) covered by artificial reefs and natural reefs. We developed multiple data-driven approaches to quantify the extent of artificial reefs within state-managed artificial reef programs, and then drew from seafloor maps and published geological and predictive seafloor habitat models to develop three estimates of natural reef extent. Comparisons of the extent of natural and artificial reefs revealed that artificial reefs account for substantially less habitat (average of two estimates 3 km 2 ; <0.01% of SEUS) in the region than natural reefs (average of three estimates 2,654 km 2 ; 2.57% of SEUS) and that this pattern holds across finer regional groupings (e.g., states, depth bins). Our overall estimates suggest that artificial reef coverage is several orders of magnitude less than natural reef coverage. While expansive seafloor mapping and characterization efforts are still needed in SEUS waters, our results fill information gaps regarding the extent of artificial and natural reef habitats in the region, providing support for ecosystem-based management, and demonstrating an approach applicable to other regions.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A fly GWAS for purine metabolites identifies human FAM214 homolog medusa, which acts in a conserved manner to enhance hyperuricemia-driven pathologies by modulating purine metabolism and the inflammatory response - Tyler A. U. Hilsabeck; Ru Liu-Bryan; Tracy Guo; Kenneth A. Wilson; Neelanjan Bose; Daniel Raftery; Jennifer N. Beck; Sven Lang; Kelly Jin; Christopher S. Nelson; Tal Oron; Marshall Stoller; et al. (GeroScience, 2022)

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Spatial Ecology of Atlantic Halibut across the Northwest Atlantic: A Recovering Species in an Era of Climate Change - Nancy L. Shackell; Jonathan A. D. Fisher; Cornelia E. den Heyer; Daniel R. Hennen; Andrew C. Seitz; Arnault Le Bris; Dominique Robert; Michael E. Kersula; Steven X. Cadrin; Richard S. McBride; Christopher H. McGuire; Tony Kess; et al. (Reviews in Fisheries Science & Aquaculture, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Long-term Annual Aerial Surveys of Submersed Aquatic Vegetation (SAV) Support Science, Management, and Restoration - Robert J. Orth; William C. Dennison; Cassie Gurbisz; Michael Hannam; Jeni Keisman; J. Brooke Landry; Jonathan S. Lefcheck; Kenneth A. Moore; Rebecca R. Murphy; Christopher J. Patrick; Jeremy Testa; Donald E. Weller; et al. (Estuaries and Coasts, 2022)
Aerial surveys of coastal habitats can uniquely inform the science and management of shallow, coastal zones, and when repeated annually, they reveal changes that are otherwise difficult to assess from ground-based surveys. This paper reviews the utility of a long-term (1984–present) annual aerial monitoring program for submersed aquatic vegetation (SAV) in Chesapeake Bay, its tidal tributaries, and nearby Atlantic coastal bays, USA. We present a series of applications that highlight the program’s importance in assessing anthropogenic impacts, gauging water quality status and trends, establishing and evaluating restoration goals, and understanding the impact of commercial fishing practices on benthic habitats. These examples demonstrate how periodically quantifying coverage of this important foundational habitat answers basic research questions locally, as well as globally, and provides essential information to resource managers. New technologies are enabling more frequent and accurate aerial surveys at greater spatial resolution and lower cost. These advances will support efforts to extend the applications described here to similar issues in other areas.

Transport Processes in the Gulf of Mexico Along the River-Estuary-Shelf-Ocean Continuum: a Review of Research from the Gulf of Mexico Research Initiative - Dubravko Justić; Villy Kourafalou; Giulio Mariotti; Songjie He; Robert Weisberg; Yannis Androulidakis; Christopher Barker; Annalisa Bracco; Brian Dzwonkowski; Chuanmin Hu; Haosheng Huang; Gregg Jacobs; et al. (Estuaries and Coasts, 2022)
Estuarine and coastal geomorphology, biogeochemistry, water quality, and coastal food webs in river-dominated shelves of the Gulf of Mexico (GoM) are modulated by transport processes associated with river inputs, winds, waves, tides, and deep-ocean/continental shelf interactions. For instance, transport processes control the fate of river-borne sediments, which in turn affect coastal land loss. Similarly, transport of freshwater, nutrients, and carbon control the dynamics of eutrophication, hypoxia, harmful algal blooms, and coastal acidification. Further, freshwater inflow transports pesticides, herbicides, heavy metals, and oil into receiving estuaries and coastal systems. Lastly, transport processes along the continuum from the rivers and estuaries to coastal and shelf areas and adjacent open ocean (abbreviated herein as “river-estuary-shelf-ocean”) regulate the movements of organisms, including the spatial distributions of individuals and the exchange of genetic information between distinct subpopulations. The Gulf of Mexico Research Initiative (GoMRI) provided unprecedented opportunities to study transport processes along the river-estuary-shelf-ocean continuum in the GoM. The understanding of transport at multiple spatial and temporal scales in this topographically and dynamically complex marginal sea was improved, allowing for more accurate forecasting of the fate of oil and other constituents. For this review, we focus on five specific transport themes: (i) wetland, estuary, and shelf exchanges; (ii) river-estuary coupling; (iii) nearshore and inlet processes; (iv) open ocean transport processes; and (v) river-induced fronts and cross-basin transport. We then discuss the relevancy of GoMRI findings on the transport processes for ecological connectivity and oil transport and fate. We also examine the implications of new findings for informing the response to future oil spills, and the management of coastal resources and ecosystems. Lastly, we summarize the research gaps identified in the many studies and offer recommendations for continuing the momentum of the research provided by the GoMRI effort. A number of uncertainties were identified that occurred in multiple settings. These include the quantification of sediment, carbon, dissolved gasses and nutrient fluxes during storms, consistent specification of the various external forcings used in analyses, methods for smooth integration of multiscale advection mechanisms across different flow regimes, dynamic coupling of the atmosphere with sub-mesoscale and mesoscale phenomena, and methods for simulating finer-scale dynamics over long time periods. Addressing these uncertainties would allow the scientific community to be better prepared to predict the fate of hydrocarbons and their impacts to the coastal ocean, rivers, and marshes in the event of another spill in the GoM.

Development of duplex qPCR targeting Carnobacterium maltaromaticum and Vagococcus salmoninarum - Isaac Standish; Rebekah McCann; Corey Puzach; Eric Leis; Jennifer Bailey; Sara Dziki; Ryan Katona; Ellen Lark; Carey Edwards; Brandon Keesler; Stephen Reichley; Stacy King; et al. (Journal of Fish Diseases, 2022)
In November 2018, Vagococcus salmoninarum was identified as the causative agent of a chronic coldwater streptococcosis epizootic in broodstock brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery in Wisconsin, USA. By February 2019, the epizootic spread to adjacent raceways containing broodstock lake trout ( Salvelinus namaycush ), whereby fish were found to be coinfected with Carnobacterium maltaromaticum and V . salmoninarum . To differentiate these two pathogens and determine the primary cause of the lake trout morbidity, a quantitative real‐time PCR (qPCR) was developed targeting the C . maltaromaticum phenylalanyl‐tRNA synthase alpha subunit ( pheS ) gene. The qPCR was combined with a V . salmoninarum qPCR, creating a duplex qPCR assay that simultaneously quantitates C. maltaromaticum and V . salmoninarum concentrations in individual lake trout tissues, and screens presumptive isolates from hatchery inspections and wild fish from national fish hatchery source waters throughout the Great Lakes basin. Vagococcus salmoninarum and C. maltaromaticum were co‐detected in broodstock brook trout from two tribal hatcheries and C. maltaromaticum was present in wild fish in source waters of several national fish hatcheries. This study provides a powerful new tool to differentiate and diagnose two emerging Gram‐positive bacterial pathogens.

Sugarcane Breeding Programs in the USA - Anna L. Hale; James R. Todd; Kenneth A. Gravois; Dimitre Mollov; Martha Malapi-Wight; Aliya Momotaz; Christopher Laborde; Ricardo Goenaga; Collins Kimbeng; Adan Solis; Herman Waguespack (Sugar Tech, 2022)

A penalized likelihood for multispecies occupancy models improves predictions of species interactions - Hannah L. Clipp; Amber L. Evans; Brin E. Kessinger; Kenneth Kellner; Christopher T. Rota (Ecology, 2021)
Multispecies occupancy models estimate dependence among multiple species of interest from patterns of co‐occurrence, but problems associated with separation and boundary estimates can lead to unreasonably large estimates of parameters and associated standard errors when species are rarely observed at the same site or when data are sparse. In this paper, we overcome these issues by implementing a penalized likelihood, which introduces a small bias in parameter estimates in exchange for a potentially large reduction in variance. We compare parameter estimates obtained from both penalized and unpenalized multispecies occupancy models fit to simulated data that exhibit various degrees of separation and to a real‐word data set of bird surveys with little apparent overlap between potentially interacting species. Our simulation results demonstrate that penalized multispecies occupancy models did not exhibit boundary estimates and produced lower bias, lower mean squared error, and improved inference relative to unpenalized models. When applied to real‐world data, our penalized multispecies occupancy model constrained boundary estimates and allowed for meaningful inference related to the interactions of two species of conservation concern. To facilitate the use of our penalized multispecies occupancy model, the techniques demonstrated in this paper have been integrated into the unmarked package in R programing language.

Neuropsychological Assessment and Screening in Heart Failure: a Meta-Analysis and Systematic Review - Eric J. Connors; Alexander O. Hauson; Brianna D. Barlet; Sharis Sarkissians; Nicholas P. Stelmach; Alyssa D. Walker; Natasha M. Nemanim; Kristina L. Greenwood; Nicholas J. Chesher; Scott C. Wollman; Kenneth E. Allen; Matthew G. Hall; et al. (Neuropsychology Review, 2021)

Locomotor Behavior and Body Mass of Paramys delicatus (Ischyromyidae, Rodentia) and Commentary on Other Early North American Paramyines - Kristen A. Prufrock; Christopher B. Ruff; Kenneth D. Rose (Journal of Mammalian Evolution, 2021)

Assessment of Flavobacterium psychrophilum ‐associated mortality in Atlantic salmon ( Salmo salar ) and brook trout ( Salvelinus fontinalis ) - Timothy J. Bruce; Jie Ma; Evan M. Jones; Brent M. Vuglar; Luke P. Oliver; Christopher Knupp; Thomas P. Loch; Kenneth D. Cain (Journal of Fish Diseases, 2021)
Salmonid diseases caused by infections of Flavobacterium psychrophilum , the causative agent of bacterial coldwater disease, remain difficult to manage as novel, pathogenic strains continue to emerge in aquaculture settings globally. To date, much of the research regarding treatment options and vaccine development has focused on rainbow trout ( Oncorhynchus mykiss ), but other inland‐reared salmonids are also impacted by this Gram‐negative bacterium. As such, Atlantic salmon ( Salmo salar ) and brook trout ( Salvelinus fontinalis ) were injection‐challenged with a variety of previously reported F. psychrophilum strains isolated from disease diagnostic cases in salmonids, as well as a standard and well‐studied F. psychrophilum strain (CSF 259–93) known to be virulent in rainbow trout. In three separate virulence assessments (Trials A, B and C), strains US063 (isolated from lake trout; Salvelinus namaycush ) and US149 (isolated from Atlantic salmon) caused a significantly higher cumulative per cent mortality (CPM) relative to other strains in Atlantic salmon ( p p =.008) and B (CPM 96% ± 2.3% vs. 81.33% ± 4.8%, p =.014). Trial C used a lower dose (1.86 × 10 8 CFU/mL) for US149, resulting in a lower mortality (78.67% ± 9.33%) relative to Trials A and B. CSF259‐93 did not cause significant mortality in any trials. In brook trout, the strain 03–179 (originally isolated from steelhead trout; Oncorhynchus mykiss ) was significantly more virulent than any other (CPM 100% ± 0%, p F. psychrophilum virulence testing in Atlantic salmon and brook trout, demonstrating the high virulence of US063 and US149 for these salmonid species. This information is applicable for the development of therapeutics and vaccines against F . psychrophilum infections and demonstrates the reproducibility of the experimental challenge model.

Cross‐protection of a live‐attenuated Flavobacterium psychrophilum immersion vaccine against novel Flavobacterium spp. and Chryseobacterium spp. strains - Timothy J. Bruce; Jie Ma; Christopher Knupp; Thomas P. Loch; Mohamed Faisal; Kenneth D. Cain (Journal of Fish Diseases, 2020)
For salmonid producers, a common threat is Flavobacterium psychrophilum . Recent advancements in bacterial coldwater disease (BCWD) management include the development of a live‐attenuated immersion vaccine that cross‐protects against an array of F. psychrophilum strains. Emerging family Flavobacteriaceae cases associated with clinical disease have been increasing, including pathogenic isolates of Flavobacterium spp. and Chryseobacterium spp. The cross‐protective ability of a live‐attenuated F. psychrophilum vaccine was determined against three virulent Flavobacteriaceae isolates. Juvenile rainbow trout were vaccinated, developed high F. psychrophilum ‐specific antibody titres and were challenged with Chryseobacterium spp. isolates (S25 and T28), a Flavobacterium sp. (S21) isolate, a mixed combination of S21:S25:T28, and a standard virulent F. psychrophilum CSF259‐93 strain. Results demonstrated strong protection in the CSF259‐93 vaccinated group (relative per cent survival (RPS)=94.44%) when compared to the relevant CSF259‐93 controls ( p p

Meta-Analysis Reveals Artificial Reefs Can Be Effective Tools for Fish Community Enhancement but Are Not One-Size-Fits-All - Avery B. Paxton; Kyle W. Shertzer; Nathan M. Bacheler; G. Todd Kellison; Kenneth L. Riley; J. Christopher Taylor (Frontiers in Marine Science, 2020)

Inhibition of Erwinia amylovora by Bacillus nakamurai - Timothy D. Leathers; Lauren P. Saunders; Michael J. Bowman; Neil P. J. Price; Kenneth M. Bischoff; Joseph O. Rich; Christopher D. Skory; Melinda S. Nunnally (Current Microbiology, 2020)

Using multiple natural tags provides evidence for extensive larval dispersal across space and through time in summer flounder - Jennifer A. Hoey; F. Joel Fodrie; Quentin A. Walker; Eric J. Hilton; G. Todd Kellison; Timothy E. Targett; J. Christopher Taylor; Kenneth W. Able; Malin L. Pinsky (Molecular Ecology, 2020)
Dispersal sets the fundamental scales of ecological and evolutionary dynamics and has important implications for population persistence. Patterns of marine dispersal remain poorly understood, partly because dispersal may vary through time and often homogenizes allele frequencies. However, combining multiple types of natural tags can provide more precise dispersal estimates, and biological collections can help to reconstruct dispersal patterns through time. We used single nucleotide polymorphism genotypes and otolith core microchemistry from archived collections of larval summer flounder ( Paralichthys dentatus , n = 411) captured between 1989 and 2012 at five locations along the US East coast to reconstruct dispersal patterns through time. Neither genotypes nor otolith microchemistry alone were sufficient to identify the source of larval fish. However, microchemistry identified clusters of larvae ( n = 3–33 larvae per cluster) that originated in the same location, and genetic assignment of clusters could be made with substantially more confidence. We found that most larvae probably originated near a biogeographical break (Cape Hatteras) and that larvae were transported in both directions across this break. Larval sources did not shift north through time, despite the northward shift of adult populations in recent decades. Our novel approach demonstrates that summer flounder dispersal is widespread throughout their range, on both intra‐ and intergenerational timescales, and may be a particularly important process for synchronizing population dynamics and maintaining genetic diversity during an era of rapid environmental change. Broadly, our results reveal the value of archived collections and of combining multiple natural tags to understand the magnitude and directionality of dispersal in species with extensive gene flow.

Vagococcus salmoninarum I—A chronic coldwater streptococcosis in broodstock brook trout ( Salvelinus fontinalis ) in Wisconsin, USA - Isaac Standish; Sara Erickson; Eric Leis; Wes Baumgartner; Thomas Loch; Christopher Knupp; Rebekah McCann; Corey Puzach; Ryan Katona; Ellen Lark; Jennifer Bailey; Jorge Buening; et al. (Journal of Fish Diseases, 2020)
In 2018, Vagococcus salmoninarum was isolated from two lots of broodstock “coaster” brook trout ( Salvelinus fontinalis ) containing ~1,500 fish at the Iron River National Fish Hatchery, at which time it was identified as the causative agent of a chronic coldwater streptococcosis epizootic. Clinical signs included exophthalmia, lethargy, erratic swimming and loss of equilibrium. Female fish experienced disproportionately higher morbidity and mortality than male co‐inhabitants, and routinely retained eggs following spawning. The most consistent gross clinical sign was heart pallor and turbid pericardial effusion. An attempted treatment using florfenicol was ineffective at halting the epizootic, which spanned more than a year and resulted in >50% mortality before remaining fish were culled. As there is no previous documentation of V. salmoninarum at this hatchery or in this species, it is still unclear what circumstances led to this epizootic. The inability to treat this chronic disease led to the loss of valuable broodstock, hampering ongoing fishery conservation efforts in the Great Lakes Basin.

Older adults demonstrate interlimb transfer of reactive gait adaptations to repeated unpredictable gait perturbations - Christopher McCrum; Kiros Karamanidis; Lotte Grevendonk; Wiebren Zijlstra; Kenneth Meijer (GeroScience, 2020)
The ability to rapidly adjust gait to cope with unexpected mechanical perturbations declines with ageing. Previous studies, however, have not ensured that gait stability pre-perturbation was equivalent across participants or age groups which may have influenced the outcomes. In this study, we investigate if age-related differences in stability following gait perturbations remain when all participants walk with equivalent stability. We also examine if interlimb transfer of gait adaptations are observed in healthy older adults, by examining if adaptation to repeated perturbations of one leg can benefit stability recovery when the other leg is perturbed. During walking at their stability-normalised walking speeds (young: 1.32 ± 0.07 m/s; older: 1.31 ± 0.13 m/s; normalised to an average margin of stability of 0.05 m), 30 young and 28 older healthy adults experienced ten unpredictable treadmill belt accelerations (the first and last applied to the right leg, the others to the left leg). Using kinematic data, we assessed the margins of stability during unperturbed walking and the first eight post-perturbation recovery steps. Older adults required three more steps to recover during the first perturbation to each leg than the young adults. Yet, after repeated perturbations of the left leg, older adults required only one more step to recover. Interestingly, for the untrained right leg, the older adults could regain stability with three fewer steps, indicating interlimb transfer of the improvements. Age differences in reactive gait stability remain even when participants’ walk with equivalent stability. Furthermore, we show that healthy older adults can transfer improvements in balance recovery made during repeated perturbations to one limb to their recovery following a perturbation to the untrained limb.

OpenMendel: a cooperative programming project for statistical genetics - Hua Zhou; Janet S. Sinsheimer; Douglas M. Bates; Benjamin B. Chu; Christopher A. German; Sarah S. Ji; Kevin L. Keys; Juhyun Kim; Seyoon Ko; Gordon D. Mosher; Jeanette C. Papp; Eric M. Sobel; et al. (Human Genetics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Urbanization impacts apex predator gene flow but not genetic diversity across an urban‐rural divide - Daryl R. Trumbo; Patricia E. Salerno; Kenneth A. Logan; Mathew W. Alldredge; Roderick B. Gagne; Christopher P. Kozakiewicz; Simona Kraberger; Nicholas M. Fountain‐Jones; Meggan E. Craft; Scott Carver; Holly B. Ernest; Kevin R. Crooks; et al. (Molecular Ecology, 2019)
Apex predators are important indicators of intact natural ecosystems. They are also sensitive to urbanization because they require broad home ranges and extensive contiguous habitat to support their prey base. Pumas ( Puma concolor ) can persist near human developed areas, but urbanization may be detrimental to their movement ecology, population structure, and genetic diversity. To investigate potential effects of urbanization in population connectivity of pumas, we performed a landscape genomics study of 130 pumas on the rural Western Slope and more urbanized Front Range of Colorado, USA. Over 12,000 single nucleotide polymorphisms (SNPs) were genotyped using double‐digest, restriction site‐associated DNA sequencing (ddRADseq). We investigated patterns of gene flow and genetic diversity, and tested for correlations between key landscape variables and genetic distance to assess the effects of urbanization and other landscape factors on gene flow. Levels of genetic diversity were similar for the Western Slope and Front Range, but effective population sizes were smaller, genetic distances were higher, and there was more admixture in the more urbanized Front Range. Forest cover was strongly positively associated with puma gene flow on the Western Slope, while impervious surfaces restricted gene flow and more open, natural habitats enhanced gene flow on the Front Range. Landscape genomic analyses revealed differences in puma movement and gene flow patterns in rural versus urban settings. Our results highlight the utility of dense, genome‐scale markers to document subtle impacts of urbanization on a wide‐ranging carnivore living near a large urban center.

Repetitive Head Impact Exposure in College Football Following an NCAA Rule Change to Eliminate Two-A-Day Preseason Practices: A Study from the NCAA-DoD CARE Consortium - Brian D. Stemper; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Stefan Duma; Jason P. Mihalik; Larry D. Riggen; Alison Brooks; Kenneth L. Cameron; Christopher C. Giza; Megan N. Houston; Jonathan Jackson; et al. (Annals of Biomedical Engineering, 2019)

Accounting for Variance in Concussion Tolerance Between Individuals: Comparing Head Accelerations Between Concussed and Physically Matched Control Subjects - Steven Rowson; Eamon T. Campolettano; Stefan M. Duma; Brian Stemper; Alok Shah; Jaroslaw Harezlak; Larry Riggen; Jason P. Mihalik; Kevin M. Guskiewicz; Christopher Giza; Alison Brooks; Kenneth Cameron; et al. (Annals of Biomedical Engineering, 2019)

Comparison of Head Impact Exposure Between Concussed Football Athletes and Matched Controls: Evidence for a Possible Second Mechanism of Sport-Related Concussion - Brian D. Stemper; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Jason P. Mihalik; Stefan M. Duma; Larry D. Riggen; Alison Brooks; Kenneth L. Cameron; Darren Campbell; John P. DiFiori; Christopher C. Giza; et al. (Annals of Biomedical Engineering, 2019)

Pattern and scale: evaluating generalities in crab distributions and marsh dynamics from small plots to a national scale - Kerstin Wasson; Kenneth Raposa; Monica Almeida; Kathryn Beheshti; Jeffrey A. Crooks; Anna Deck; Nikki Dix; Caitlin Garvey; Jason Goldstein; David Samuel Johnson; Scott Lerberg; Pamela Marcum; et al. (Ecology, 2019)
The generality of ecological patterns depends inextricably on the scale at which they are examined. We investigated patterns of crab distribution and the relationship between crabs and vegetation in salt marshes at multiple scales. By using consistent monitoring protocols across 15 U.S. National Estuarine Research Reserves, we were able to synthesize patterns from the scale of quadrats to the entire marsh landscape to regional and national scales. Some generalities emerged across marshes from our overall models, and these are useful for informing broad coastal management policy. We found that crab burrow distribution within a marsh could be predicted by marsh elevation, distance to creek and soil compressibility. While these physical factors also affected marsh vegetation cover, we did not find a strong or consistent overall effect of crabs at a broad scale in our multivariate model, though regressions conducted separately for each site revealed that crab burrows were negatively correlated with vegetation cover at 4 out of 15 sites. This contrasts with recent smaller‐scale studies and meta‐analyses synthesizing such studies that detected strong negative effects of crabs on marshes, likely because we sampled across the entire marsh landscape, while targeted studies are typically limited to low‐lying areas near creeks, where crab burrow densities are highest. Our results suggest that sea‐level rise generally poses a bigger threat to marshes than crabs, but there will likely be interactions between these physical and biological factors. Beyond these generalities across marshes, we detected some regional differences in crab community composition, richness, and abundance. However, we found striking differences among sites within regions, and within sites, in terms of crab abundance and relationships to marsh integrity. Although generalities are broadly useful, our findings indicate that local managers cannot rely on data from other nearby systems, but rather need local information for developing salt marsh management strategies.

Observational Needs of Sea Surface Temperature - Anne G. O’Carroll; Edward M. Armstrong; Helen M. Beggs; Marouan Bouali; Kenneth S. Casey; Gary K. Corlett; Prasanjit Dash; Craig J. Donlon; Chelle L. Gentemann; Jacob L. Høyer; Alexander Ignatov; Kamila Kabobah; et al. (Frontiers in Marine Science, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Front Cover - Jie Ma; Timothy J. Bruce; Ponnerassery S. Sudheesh; Christopher Knupp; Thomas P. Loch; Mohamed Faisal; Kenneth D. Cain (Journal of Fish Diseases, 2019)

Assessment of cross‐protection to heterologous strains of Flavobacterium psychrophilum following vaccination with a live‐attenuated coldwater disease immersion vaccine - Jie Ma; Timothy J. Bruce; Ponnerassery S. Sudheesh; Christopher Knupp; Thomas P. Loch; Mohamed Faisal; Kenneth D. Cain (Journal of Fish Diseases, 2019)
Bacterial coldwater disease, caused by Flavobacterium psychrophilum , remains one of the most significant bacterial diseases of salmonids worldwide. A previously developed and reported live‐attenuated immersion vaccine ( F. psychrophilum ; B.17‐ ILM ) has been shown to confer significant protection to salmonids. To further characterize this vaccine, a series of experiments were carried out to determine the cross‐protective efficacy of this B.17‐ ILM vaccine against 9 F. psychrophilum isolates (representing seven sequence types/three clonal complexes as determined by multilocus sequence typing) in comparison with a wild‐type virulent strain, CSF ‐259‐93. To assess protection, 28‐day experimental challenges of rainbow trout ( Oncorhynchus mykiss ) fry were conducted following immersion vaccinations with the B.17‐ ILM vaccine. F. psychrophilum strains used in challenge trials were isolated from several fish species across the globe; however, all were found to be virulent in rainbow trout. The B.17‐ ILM vaccine provided significant protection against all strains, with relative percent survival values ranging from 51% to 72%. All vaccinated fish developed an adaptive immune response (as measured by F. psychrophilum‐ specific antibodies) that increased out to the time of challenge (8 weeks postimmunization). Previous studies have confirmed that antibody plays an important role in protection against F. psychrophilum challenge; therefore, specific antibodies to the B.17‐ ILM vaccine strain appear to contribute to the cross‐protection observed to heterologous strain. The ability of such antibodies to bind to similar antigenic regions for all strains was confirmed by western blot analyses. Results presented here support the practical application of this live‐attenuated vaccine, and suggest that it will be efficacious even in aquaculture operations affected by diverse strains of F. psychrophilum .

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Effect of torpor on host transcriptomic responses to a fungal pathogen in hibernating bats - Kenneth A. Field; Brent J. Sewall; Jenni M. Prokkola; Gregory G. Turner; Marianne F. Gagnon; Thomas M. Lilley; J. Paul White; Joseph S. Johnson; Christopher L. Hauer; DeeAnn M. Reeder (Molecular Ecology, 2018)
Hibernation, the use of prolonged torpor to depress metabolism, is employed by mammals to conserve resources during extended periods of extreme temperatures and/or resource limitation. Mammalian hibernators arouse to euthermy periodically during torpor for reasons that are not well understood, and these arousals may facilitate immune processes. To determine whether arousals enable host responses to pathogens, we used dual RNA ‐Seq and a paired sampling approach to examine gene expression in a hibernating bat, the little brown myotis ( Myotis lucifugus ). During torpor, transcript levels differed in only a few genes between uninfected wing tissue and adjacent tissue infected with Pseudogymnoascus destructans , the fungal pathogen that causes white‐nose syndrome. Within 70–80 min after emergence from torpor, large changes in gene expression were observed due to local infection, particularly in genes involved in pro‐inflammatory host responses to fungal pathogens, but also in many genes involved in immune responses and metabolism. These results support the hypothesis that torpor is a period of relative immune dormancy and arousals allow for local immune responses in infected tissues during hibernation. Host–pathogen interactions were also found to regulate gene expression in the pathogen differently depending on the torpor state of the host. Hibernating species must balance the benefits of energy and water conservation achieved during torpor with the costs of decreased immune competence. Interbout arousals allow hibernators to optimize these, and other, trade‐offs during prolonged hibernation by enabling host responses to pathogens within brief, periodic episodes of euthermy.

Evaluating Tidal Wetland Restoration Performance Using National Estuarine Research Reserve System Reference Sites and the Restoration Performance Index (RPI) - Kenneth B. Raposa; Scott Lerberg; Craig Cornu; John Fear; Nina Garfield; Christopher Peter; Robin L.J. Weber; Gregg Moore; David Burdick; Michelle Dionne (Estuaries and Coasts, 2018)

Functional connectivity abnormalities and associated cognitive deficits in fetal alcohol Spectrum disorders (FASD) - Jeffrey R. Wozniak; Bryon A. Mueller; Sarah N. Mattson; Claire D. Coles; Julie A. Kable; Kenneth L. Jones; Christopher J. Boys; Kelvin O. Lim; Edward P. Riley; Elizabeth R. Sowell (Brain Imaging and Behavior, 2017)

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

Modeling brain lentiviral infections during antiretroviral therapy in AIDS - Weston C. Roda; Michael Y. Li; Michael S. Akinwumi; Eugene L. Asahchop; Benjamin B. Gelman; Kenneth W. Witwer; Christopher Power (Journal of NeuroVirology, 2017)

Specification of a Coupled Geological and Wellbore Fluid Dynamics Model for Uncertainty Analysis and Risk-Based Design on a Subsea Oil Project - Christopher J. Jablonowski; Arash Haghshenas; Edward E. Shumilak; Kenneth F. Tyler (Natural Resources Research, 2017)

Aging and the effects of a half marathon on Achilles tendon force–elongation relationship - Thijs Maria Anne Ackermans; Gaspar Epro; Christopher McCrum; Kai Daniel Oberländer; Frank Suhr; Maarten Robert Drost; Kenneth Meijer; Kiros Karamanidis (European Journal of Applied Physiology, 2016)

Comparing Measures of Estuarine Ecosystem Production in a Temperate New England Estuary - Autumn Oczkowski; Christopher W. Hunt; Kenneth Miller; Candace Oviatt; Scott Nixon; Leslie Smith (Estuaries and Coasts, 2016)

Late Pleistocene climate inferences from a water balance model of Jakes Valley, Nevada (USA) - Cornelia Barth; Douglas P. Boyle; Benjamin J. Hatchett; Scott D. Bassett; Christopher B. Garner; Kenneth D. Adams (Journal of Paleolimnology, 2016)

Measuring Microhabitat Temperature in Arboreal Primates: A Comparison of On-Animal and Stationary Approaches - Cynthia L. Thompson; Susan H. Williams; Kenneth E. Glander; Christopher J. Vinyard (International Journal of Primatology, 2016)

Experimental and theoretical correlations between vanadium K-edge X-ray absorption and K $$\varvec{β} $$ β emission spectra - Julian A. Rees; Aleksandra Wandzilak; Dimitrios Maganas; Nicole I. C. Wurster; Stefan Hugenbruch; Joanna K. Kowalska; Christopher J. Pollock; Frederico A. Lima; Kenneth D. Finkelstein; Serena DeBeer (JBIC Journal of Biological Inorganic Chemistry, 2016)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Preclinical Pharmacokinetics Study of R- and S-Enantiomers of the Histone Deacetylase Inhibitor, AR-42 (NSC 731438), in Rodents - Hao Cheng; Zhiliang Xie; William P. Jones; Xiaohui Tracey Wei; Zhongfa Liu; Dasheng Wang; Samuel K. Kulp; Jiang Wang; Christopher C. Coss; Ching-Shih Chen; Guido Marcucci; Ramiro Garzon; et al. (The AAPS Journal, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Critical biogeochemical functions in the subsurface are associated with bacteria from new phyla and little studied lineages - Laura A. Hug; Brian C. Thomas; Itai Sharon; Christopher T. Brown; Ritin Sharma; Robert L. Hettich; Michael J. Wilkins; Kenneth H. Williams; Andrea Singh; Jillian F. Banfield (Environmental Microbiology, 2016)
Summary Nitrogen, sulfur and carbon fluxes in the terrestrial subsurface are determined by the intersecting activities of microbial community members, yet the organisms responsible are largely unknown. Metagenomic methods can identify organisms and functions, but genome recovery is often precluded by data complexity. To address this limitation, we developed subsampling assembly methods to re‐construct high‐quality draft genomes from complex samples. We applied these methods to evaluate the interlinked roles of the most abundant organisms in biogeochemical cycling in the aquifer sediment. Community proteomics confirmed these activities. The eight most abundant organisms belong to novel lineages, and two represent phyla with no previously sequenced genome. Four organisms are predicted to fix carbon via the C alvin– B enson– B assham, W ood– L jungdahl or 3‐hydroxyproprionate/4‐hydroxybutarate pathways. The profiled organisms are involved in the network of denitrification, dissimilatory nitrate reduction to ammonia, ammonia oxidation and sulfate reduction/oxidation, and require substrates supplied by other community members. An ammonium‐oxidizing T haumarchaeote is the most abundant community member, despite low ammonium concentrations in the groundwater. This organism likely benefits from two other relatively abundant organisms capable of producing ammonium from nitrate, which is abundant in the groundwater. Overall, dominant members of the microbial community are interconnected through exchange of geochemical resources.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Production of novel types of antibacterial liamocins by diverse strains of Aureobasidium pullulans grown on different culture media - Timothy D. Leathers; Neil P. J. Price; Kenneth M. Bischoff; Pennapa Manitchotpisit; Christopher D. Skory (Biotechnology Letters, 2015)

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

siRNA-Mediated Knockdown of P450 Oxidoreductase in Rats: A Tool to Reduce Metabolism by CYPs and Increase Exposure of High Clearance Compounds - Rob S. Burke; Inthirai Somasuntharam; Paul Rearden; Duncan Brown; Sujal V. Deshmukh; Martha A. DiPietro; Jillian DiMuzio; Roy Eisenhandler; Scott E. Fauty; Christopher Gibson; Marian E. Gindy; Kelly A. Hamilton; et al. (Pharmaceutical Research, 2014)

Residence Times and Decay Rates of Downed Woody Debris Biomass/Carbon in Eastern US Forests - Matthew B. Russell; Christopher W. Woodall; Shawn Fraver; Anthony W. D’Amato; Grant M. Domke; Kenneth E. Skog (Ecosystems, 2014)

Regional brain distribution of translocator protein using [11C]DPA-713 PET in individuals infected with HIV - Jennifer M. Coughlin; Yuchuan Wang; Shuangchao Ma; Chen Yue; Pearl K. Kim; Ashley V. Adams; Heidi V. Roosa; Kenneth L. Gage; Marigo Stathis; Rana Rais; Camilo Rojas; Jennifer L. McGlothan; et al. (Journal of NeuroVirology, 2014)

Prevalence of HOXB13 mutation in a population of Ashkenazi Jewish men treated for prostate cancer - Shaheen Alanee; Sohela Shah; Joseph Vijai; Kasmintan Schrader; Robert Hamilton; Rohini Rau-Murthy; Kara Sarrel; Christopher Manschreck; James Eastham; Kenneth Offit (Familial Cancer, 2013)

Development of a Maleimide Amino Acid for Use as a Tool for Peptide Conjugation and Modification - Kenneth Christopher Koehler; Daniel L. Alge; Kristi S. Anseth; Christopher N. Bowman (International Journal of Peptide Research and Therapeutics, 2013)

Multiscale assessment of green leaf cover in a semi-arid rangeland with a small unmanned aerial vehicle - Kenneth C. McGwire; Mark A. Weltz; Julie A. Finzel; Christopher E. Morris; Lynn F. Fenstermaker; David S. McGraw (International Journal of Remote Sensing, 2013)

Characterization of fracture connectivity in a siliciclastic bedrock aquifer near a public supply well (Wisconsin, USA) - Christopher A. Gellasch; Kenneth R. Bradbury; David J. Hart; Jean M. Bahr (Hydrogeology Journal, 2013)

Development and characterization of twenty-two novel microsatellite markers for the mountain whitefish, Prosopium williamsoni and cross-amplification in the round whitefish, P. cylindraceum, using paired-end Illumina shotgun sequencing - Jason O’Bryhim; Christopher Somers; Stacey L. Lance; Monica Yau; Douglas R. Boreham; Kenneth L. Jones; Eric B. Taylor (Conservation Genetics Resources, 2013)

Spatial mapping of extracellular oxidant production by a white rot basidiomycete on wood reveals details of ligninolytic mechanism - Christopher G. Hunt; Carl J. Houtman; Don C. Jones; Peter Kitin; Premsagar Korripally; Kenneth E. Hammel (Environmental Microbiology, 2013)
Summary Oxidative cleavage of the recalcitrant plant polymer lignin is a crucial step in global carbon cycling, and is accomplished most efficiently by fungi that cause white rot of wood. These basidiomycetes secrete many enzymes and metabolites with proposed ligninolytic roles, and it is not clear whether all of these agents are physiologically important during attack on natural lignocellulosic substrates. One new approach to this problem is to infer properties of ligninolytic oxidants from their spatial distribution relative to the fungus on the lignocellulose. We grew P hanerochaete chrysosporium on wood sections in the presence of oxidant‐sensing beads based on the ratiometric fluorescent dye BODIPY 581/591. The beads, having fixed locations relative to the fungal hyphae, enabled spatial mapping of cumulative extracellular oxidant distributions by confocal fluorescence microscopy. The results showed that oxidation gradients occurred around the hyphae, and data analysis using a mathematical reaction–diffusion model indicated that the dominant oxidant during incipient white rot had a half‐life under 0.1 s. The best available hypothesis is that this oxidant is the cation radical of the secreted P . chrysosporium metabolite veratryl alcohol.

Time-dependent changes in glucose and insulin regulation during intermittent hypoxia and continuous hypoxia - Euhan J. Lee; Laura C. Alonso; Darko Stefanovski; Hilary C. Strollo; Lia C. Romano; Baobo Zou; Srikanth Singamsetty; Keith A. Yester; Kenneth R. McGaffin; Adolfo Garcia-Ocana; Christopher P. O’Donnell (European Journal of Applied Physiology, 2013)

Relationship between anthropometric factors, radiation exposure, and colon cancer incidence in the Life Span Study cohort of atomic bomb survivors - Erin O. Semmens; Kenneth J. Kopecky; Eric Grant; Robert W. Mathes; Nobuo Nishi; Hiromi Sugiyama; Hiroko Moriwaki; Ritsu Sakata; Midori Soda; Fumiyoshi Kasagi; Michiko Yamada; Saeko Fujiwara; et al. (Cancer Causes & Control, 2013)

An acoustic investigation of seagrass photosynthesis - Christopher J. Wilson; Preston S. Wilson; Kenneth H. Dunton (Marine Biology, 2012)

Methods for Studying the Ecological Physiology of Feeding in Free-Ranging Howlers (Alouatta palliata) at La Pacifica, Costa Rica - Christopher J. Vinyard; Kenneth E. Glander; Mark F. Teaford; Cynthia L. Thompson; Max Deffenbaugh; Susan H. Williams (International Journal of Primatology, 2012)

Does phylogeny matter? Assessing the impact of phylogenetic information in ecological meta‐analysis - Scott A. Chamberlain; Stephen M. Hovick; Christopher J. Dibble; Nick L. Rasmussen; Benjamin G. Van Allen; Brian S. Maitner; Jeffrey R. Ahern; Lukas P. Bell‐Dereske; Christopher L. Roy; Maria Meza‐Lopez; Juli Carrillo; Evan Siemann; et al. (Ecology Letters, 2012)
Meta‐analysis is increasingly used in ecology and evolutionary biology. Yet, in these fields this technique has an important limitation: phylogenetic non‐independence exists among taxa, violating the statistical assumptions underlying traditional meta‐analytic models. Recently, meta‐analytical techniques incorporating phylogenetic information have been developed to address this issue. However, no syntheses have evaluated how often including phylogenetic information changes meta‐analytic results. To address this gap, we built phylogenies for and re‐analysed 30 published meta‐analyses, comparing results for traditional vs. phylogenetic approaches and assessing which characteristics of phylogenies best explained changes in meta‐analytic results and relative model fit. Accounting for phylogeny significantly changed estimates of the overall pooled effect size in 47% of datasets for fixed‐effects analyses and 7% of datasets for random‐effects analyses. Accounting for phylogeny also changed whether those effect sizes were significantly different from zero in 23 and 40% of our datasets (for fixed‐ and random‐effects models, respectively). Across datasets, decreases in pooled effect size magnitudes after incorporating phylogenetic information were associated with larger phylogenies and those with stronger phylogenetic signal. We conclude that incorporating phylogenetic information in ecological meta‐analyses is important, and we provide practical recommendations for doing so.

Scale-dependent neighborhood effects: shared doom and associational refuge - Sara E. Emerson; Joel S. Brown; Christopher J. Whelan; Kenneth A. Schmidt (Oecologia, 2012)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Life history and habitat use of the speckled worm eel, Myrophis punctatus, along the east coast of the United States - Kenneth W. Able; Dennis M. Allen; Gretchen Bath-Martin; Jonathan A. Hare; Donald E. Hoss; Katrin E. Marancik; Perce M. Powles; David E. Richardson; J. Christopher Taylor; Harvey J. Walsh; Stanley M. Warlen; Charles Wenner (Environmental Biology of Fishes, 2011)

Transient Supplementation of Anabolic Growth Factors Rapidly Stimulates Matrix Synthesis in Engineered Cartilage - Kenneth W. Ng; Christopher J. O’Conor; Lindsay E. Kugler; James L. Cook; Gerard A. Ateshian; Clark T. Hung (Annals of Biomedical Engineering, 2011)

Relations of hydrogeologic factors, groundwater reduction-oxidation conditions, and temporal and spatial distributions of nitrate, Central-Eastside San Joaquin Valley, California, USA - Matthew K. Landon; Christopher T. Green; Kenneth Belitz; Michael J. Singleton; Bradley K. Esser (Hydrogeology Journal, 2011)

Dipyridamole Treatment Prior to Stroke Onset: Examining Post-stroke Cerebral Circulation and Outcome in Rabbits - Christopher D. d’Esterre; Kenneth M. Tichauer; Richard I. Aviv; Wolfgang Eisert; Ting-Yim Lee (Translational Stroke Research, 2011)

The effect of vitamin B 12 on phytoplankton growth and community structure in the Gulf of Alaska - Florian Koch; Maria Alejandra Marcoval; Caterina Panzeca; Kenneth W. Bruland; Sergio A. Sañudo-Wilhelmy; Christopher J. Gobler (Limnology and Oceanography, 2011)
A majority of eukaryotic phytoplankton species require an exogenous source of vitamin B 12 for growth and recent field studies in some coastal and polar regions indicate that the addition of vitamin B 12 alone, or with another limiting nutrient can influence the accumulation of phytoplankton biomass. We quantified the concentrations and uptake rates of vitamin B 12 , characterized phytoplankton community composition, and examined the ability of vitamin B 12 to alter the growth and composition of phytoplankton communities in the Gulf of Alaska. Picoplankton (0.2–2 μm) were responsible for the majority of vitamin B 12 uptake in both coastal and high‐nutrient low‐chlorophyll (HNLC) regions and B 12 concentrations and uptake rates were higher in HNLC regions compared to coastal regions with higher iron (Fe) concentrations. During vitamin amendment experiments, B 12 alone or in conjunction with other limiting nutrients (N or Fe) significantly enhanced algal biomass and increased the growth rates of multiple groups of larger (> 2 μm) phytoplankton. This included ecologically significant, B 12 auxotrophs such as Gymnodinium sp. and Alexandrium sp. (in the costal experiment) as well as Chaetoceros sp. and Gymnodinium sp. (in the HNLC experiment). The ability of vitamin B 12 to shape algal community composition in coastal and HNLC areas of the Gulf of Alaska, even in cases where it does not limit total phytoplankton production, suggests that it may influence carbon export in this and other polar ecosystems.

Managed Forest Carbon Estimates for the US Greenhouse Gas Inventory, 1990—2008 - Linda S. Heath; James E. Smith; Kenneth E. Skog; David J. Nowak; Christopher W. Woodall (Journal of Forestry, 2011)
Land-use change and forestry is the major category featuring carbon sequestration in the annual US Greenhouse Gas Inventory, required by the United Nations Framework Convention on Climate Change. We describe the National Greenhouse Gas Inventory and present the sources of our data and methods and the most recent results. Forests and forest products in the United States sequestered more than −790 million metric tn of CO2 equivalent in 2008, on 253 million ha of forestland. This estimate represents a net increase in carbon, including effects of growth, harvests, or other disturbances of forest ecosystems, as well as carbon stored in harvested wood products. Both area and carbon density of these forestlands have increased since 1990, the first year estimates are required. Currently, 89% of net annual sequestration is in the forest ecosystem, and the balance is net carbon addition to harvested wood products.

Recent and Historic Drivers of Landscape Change in the Everglades Ridge, Slough, and Tree Island Mosaic - Laurel Larsen; Nicholas Aumen; Christopher Bernhardt; Vic Engel; Thomas Givnish; Scot Hagerthey; Judson Harvey; Lynn Leonard; Paul McCormick; Christopher Mcvoy; Gregory Noe; Martha Nungesser; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Ligand-Binding Mass Spectrometry to Study Biotransformation of Fusion Protein Drugs and Guide Immunoassay Development: Strategic Approach and Application to Peptibodies Targeting the Thrombopoietin Receptor - Michael P. Hall; Colin Gegg; Kenneth Walker; Christopher Spahr; Robert Ortiz; Vimal Patel; Steven Yu; Liana Zhang; Hsieng Lu; Binodh DeSilva; Jean W. Lee (The AAPS Journal, 2010)

Multicomponent Amorphous Nanofibers Electrospun from Hot Aqueous Solutions of a Poorly Soluble Drug - Deng-Guang Yu; Li-Dong Gao; Kenneth White; Christopher Branford-White; Wei-Yue Lu; Li-Min Zhu (Pharmaceutical Research, 2010)

Regulation of glucose-6-phosphate dehydrogenase by reversible phosphorylation in liver of a freeze tolerant frog - Christopher A. Dieni; Kenneth B. Storey (Journal of Comparative Physiology B, 2010)

Dissolution Improvement of Electrospun Nanofiber-Based Solid Dispersions for Acetaminophen - Deng-Guang Yu; Christopher Branford-White; Kenneth White; Xue-Lian Li; Li-Min Zhu (AAPS PharmSciTech, 2010)

Microclimate and limits to photosynthesis in a diverse community of hypolithic cyanobacteria in northern Australia - Christopher R. Tracy; Claire Streten‐Joyce; Robert Dalton; Kenneth E. Nussear; Karen S. Gibb; Keith A. Christian (Environmental Microbiology, 2010)
Summary Hypolithic microbes, primarily cyanobacteria, inhabit the highly specialized microhabitats under translucent rocks in extreme environments. Here we report findings from hypolithic cyanobacteria found under three types of translucent rocks (quartz, prehnite, agate) in a semiarid region of tropical Australia. We investigated the photosynthetic responses of the cyanobacterial communities to light, temperature and moisture in the laboratory, and we measured the microclimatic variables of temperature and soil moisture under rocks in the field over an annual cycle. We also used molecular techniques to explore the diversity of hypolithic cyanobacteria in this community and their phylogenetic relationships within the context of hypolithic cyanobacteria from other continents. Based on the laboratory experiments, photosynthetic activity required a minimum soil moisture of 15% (by mass). Peak photosynthetic activity occurred between approximately 8°C and 42°C, though some photosynthesis occurred between −1°C and 51°C. Maximum photosynthesis rates also occurred at light levels of approximately 150–550 μmol m −2 s −1 . We used the field microclimatic data in conjunction with these measurements of photosynthetic efficiency to estimate the amount of time the hypolithic cyanobacteria could be photosynthetically active in the field. Based on these data, we estimated that conditions were appropriate for photosynthetic activity for approximately 942 h (∼75 days) during the year. The hypolithic cyanobacteria community under quartz, prehnite and agate rocks was quite diverse both within and between rock types. We identified 115 operational taxonomic units (OTUs), with each rock hosting 8–24 OTUs. A third of the cyanobacteria OTUs from northern Australia grouped with Chroococcidiopsis , a genus that has been identified from hypolithic and endolithic communities from the Gobi, Mojave, Atacama and Antarctic deserts. Several OTUs identified from northern Australia have not been reported to be associated with hypolithic communities previously.

The regulation of AMPK signaling in a natural state of profound metabolic rate depression - Christopher J. Ramnanan; David C. McMullen; Amy G. Groom; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2010)

The pharmacokinetics and pharmacodynamics of prasugrel in healthy Chinese, Japanese, and Korean subjects compared with healthy Caucasian subjects - David S. Small; Prajakti Kothare; Eunice Yuen; D. Richard Lachno; Ying G. Li; Kenneth J. Winters; Nagy A. Farid; Lan Ni; Joseph A. Jakubowski; Daniel E. Salazar; Vivian T. Thieu; Christopher D. Payne (European Journal of Clinical Pharmacology, 2010)

THE GODAE HIGH-RESOLUTION SEA SURFACE TEMPERATURE PILOT PROJECT - Craig Donlon; Kenneth Casey; Ian Robinson; Chelle Gentemann; Richard Reynolds; Ian Barton; Olivier Arino; John Stark; Nick Rayner; Pierre LeBorgne; David Poulter; Jorge Vazquez-Cuervo; et al. (Oceanography, 2009)

Understanding Causes and Impacts of the Dinoflagellate, Cochlodinium polykrikoides, Blooms in the Chesapeake Bay - Margaret R. Mulholland; Ryan E. Morse; George E. Boneillo; Peter W. Bernhardt; Katherine C. Filippino; Leo A. Procise; Jose L. Blanco-Garcia; Harold G. Marshall; Todd A. Egerton; William S. Hunley; Kenneth A. Moore; Dianna L. Berry; et al. (Estuaries and Coasts, 2009)

Arctic Lake Physical Processes and Regimes with Implications for Winter Water Availability and Management in the National Petroleum Reserve Alaska - Benjamin M. Jones; Christopher D. Arp; Kenneth M. Hinkel; Richard A. Beck; Joel A. Schmutz; Barry Winston (Environmental Management, 2009)

Regulation of global protein translation and protein degradation in aerobic dormancy - Christopher J. Ramnanan; Marcus E. Allan; Amy G. Groom; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2009)

Telemetry System for Assessing Jaw-Muscle Function in Free-ranging Primates - Susan H. Williams; Christopher J. Vinyard; Kenneth E. Glander; Max Deffenbaugh; Mark F. Teaford; Cynthia L. Thompson (International Journal of Primatology, 2008)

Putative native source of the invasive fire ant Solenopsis invicta in the USA - Eric J. Caldera; Kenneth G. Ross; Christopher J. DeHeer; D. DeWayne Shoemaker (Biological Invasions, 2008)

Initial nicotine sensitivity in humans as a function of impulsivity - Kenneth A. Perkins; Caryn Lerman; Sarah B. Coddington; Christopher Jetton; Joshua L. Karelitz; John A. Scott; Annette S. Wilson (Psychopharmacology, 2008)

The complete nucleotide sequence of the cassava (Manihot esculenta) chloroplast genome and the evolution of atpF in Malpighiales: RNA editing and multiple losses of a group II intron - Henry Daniell; Kenneth J. Wurdack; Anderson Kanagaraj; Seung-Bum Lee; Christopher Saski; Robert K. Jansen (Theoretical and Applied Genetics, 2008)

Adverse effects from environmental mercury loads on breeding common loons - David C. Evers; Lucas J. Savoy; Christopher R. DeSorbo; David E. Yates; William Hanson; Kate M. Taylor; Lori S. Siegel; John H. Cooley; Michael S. Bank; Andrew Major; Kenneth Munney; Barry F. Mower; et al. (Ecotoxicology, 2008)

The regulation of thapsigargin-sensitive sarcoendoplasmic reticulum Ca2+-ATPase activity in estivation - Christopher J. Ramnanan; Kenneth B. Storey (Journal of Comparative Physiology B, 2008)

Corrigendum: 2007 highlights of advances in the pharmaceutical sciences: An American Association of Pharmaceutical Scientists (AAPS) perspective - Marilyn N. Martinez; Peter Bonate; Robert L. Chapman; Anne De Groot; Susan D'Souza; Naushad Ghilazi; Vivian Gray; Vishal K. Gupta; Kim Huynh-Ba; Sunil Iyer; Arya Jayatilaka; Amita Joshi; et al. (The AAPS Journal, 2007)

2007 highlights of advances in the pharmaceutical sciences: An American Association of Pharmaceutical Scientists (AAPS) perspective - Marilyn N. Martinez; Peter Bonate; Robert L. Chapman; Anne De Groot; Susan D'Souza; Naushad Ghilazi; Vivian Gray; Vishal K. Gupta; Kim Huynh-Ba; Sunil Iyer; Arya Jayatilaka; Amita Joshi; et al. (The AAPS Journal, 2007)

Structure and function of ABC transporters: the ATP switch provides flexible control - Kenneth J. Linton; Christopher F. Higgins (Pflügers Archiv - European Journal of Physiology, 2007)

Fungal hydroquinones contribute to brown rot of wood - Melissa R. Suzuki; Christopher G. Hunt; Carl J. Houtman; Zachary D. Dalebroux; Kenneth E. Hammel (Environmental Microbiology, 2006)
Summary The fungi that cause brown rot of wood initiate lignocellulose breakdown with an extracellular Fenton system in which Fe 2+ and H 2 O 2 react to produce hydroxyl radicals (·OH), which then oxidize and cleave the wood holocellulose. One such fungus, Gloeophyllum trabeum , drives Fenton chemistry on defined media by reducing Fe 3+ and O 2 with two extracellular hydroquinones, 2,5‐dimethoxyhydroquinone (2,5‐DMHQ) and 4,5‐dimethoxycatechol (4,5‐DMC). However, it has never been shown that the hydroquinones contribute to brown rot of wood. We grew G. trabeum on spruce blocks and found that 2,5‐DMHQ and 4,5‐DMC were each present in the aqueous phase at concentrations near 20 μM after 1 week. We determined rate constants for the reactions of 2,5‐DMHQ and 4,5‐DMC with the Fe 3+ ‐oxalate complexes that predominate in wood undergoing brown rot, finding them to be 43 l mol −1 s −1 and 65 l mol −1 s −1 respectively. Using these values, we estimated that the average amount of hydroquinone‐driven ·OH production during the first week of decay was 11.5 μmol g −1 dry weight of wood. Viscometry of the degraded wood holocellulose coupled with computer modelling showed that a number of the same general magnitude, 41.2 μmol oxidations per gram, was required to account for the depolymerization that occurred in the first week. Moreover, the decrease in holocellulose viscosity was correlated with the measured concentrations of hydroquinones. Therefore, hydroquinone‐driven Fenton chemistry is one component of the biodegradative arsenal that G. trabeum expresses on wood.

Genetic mapping of expressed sequences in onion and in silico comparisons with rice show scant colinearity - William J. Martin; John McCallum; Masayoshi Shigyo; Jernej Jakse; Joseph C. Kuhl; Naoko Yamane; Meeghan Pither-Joyce; Ali Fuat Gokce; Kenneth C. Sink; Christopher D. Town; Michael J. Havey (Molecular Genetics and Genomics, 2005)

Naltrexone reduces the relative reinforcing value of nicotine in a cigarette smoking choice paradigm - Margaret Rukstalis; Christopher Jepson; Andrew Strasser; Kevin G. Lynch; Kenneth Perkins; Freda Patterson; Caryn Lerman (Psychopharmacology, 2005)

Coastal Ocean Physics and Red Tides: An Example from Monterey Bay, California - John Ryan; Heidi Dierssen; Raphael Kudela; Christopher Scholin; Kenneth Johnson; James Sullivan; Andrew Fischer; Erich Rienecker; Patrick McEnaney; Francisco Chavez (Oceanography, 2005)

Heme-copper/dioxygen adduct formation relevant to cytochrome c oxidase: spectroscopic characterization of [(6L)FeIII-(O22?)-CuII]+ - Reza A. Ghiladi; Hong-wei Huang; Pierre Monne-Loccoz; Jay Stasser; Ninian J. Blackburn; Amina S. Woods; Robert J. Cotter; Christopher D. Incarvito; Arnold L. Rheingold; Kenneth D. Karlin (JBIC Journal of Biological Inorganic Chemistry, 2005)

The relationship between species detection probability and local extinction probability - Russell Alpizar-Jara; James D. Nichols; James E. Hines; John R. Sauer; Kenneth H. Pollock; Christopher S. Rosenberry (Oecologia, 2004)

The effects of scale: variation in the APOA1/C3/A4/A5 gene cluster - Andrew G. Clark; Deborah A. Nickerson; Kenneth M. Weiss; Veikko Salomaa; Eric Boerwinkle; Stephanie M. Fullerton; Anne V. Buchanan; Vibhor A. Sonpar; Jari H. Stengrd; Joshua D. Smith; Scott L. Taylor; Christopher S. Carlson (Human Genetics, 2004)

Subjective effects of an initial dose of nicotine nasal spray predict treatment outcome - Margaret Rukstalis; Kenneth Perkins; Janet Audrain-McGovern; Caryn Lerman; Christopher Jepson; Vyga Kaufmann (Psychopharmacology, 2004)

Definition of the domain boundaries is critical to the expression of the nucleotide-binding domains of P-glycoprotein - Ian D. Kerr; Georgina Berridge; Kenneth J. Linton; Christopher F. Higgins; Richard Callaghan (European Biophysics Journal, 2003)

Analysis of costimulation by 4-1BBL, CD40L, and B7 in graft rejection by gene expression profiles - Rachel DeFina; Kenneth Christopher; Hongzhen He; Didier Mandelbrot; Yongping Gu; Patricia Finn; David L. Perkins (Journal of Molecular Medicine, 2003)

A new progressive ratio schedule for support of morphine self-administration in opiate dependent rats - Kenneth Grasing; Ning Li; Shaunteng He; Christopher Parrish; John Delich; John Glowa (Psychopharmacology, 2003)

Aminosalicylic acid reduces the antiproliferative effect of hyperglycaemia, advanced glycation endproducts and glycated basic fibroblast growth factor in cultured bovine aortic endothelial cells: Comparison with aminoguanidine - Yasotha Duraisamy; John Gaffney; Mark Slevin; Christopher A. Smith; Kenneth Williamson; Nessar Ahmed (Molecular and Cellular Biochemistry, 2003)

A computer image analysis system for microvessel density measurement in solid tumours - Jonathan Charles Goddard; Christopher Derek Sutton; Peter N. Furness; Roger Clive Kockelbergh; Kenneth John O'Byrne (Angiogenesis, 2002)

Thermal and Bioenergetics of Elasmobranchs: Bridging the Gap - Christopher G. Lowe; Kenneth J. Goldman (Environmental Biology of Fishes, 2001)

Factors Affecting Population Assessments of Desert Tortoises - Jerome E. Freilich; Kenneth P. Burnham; Christopher M. Collins; C. Ann Garry (Conservation Biology, 2000)
Desert tortoises have been a subject of controversy since their listing as threatened in 1990. With a wide geographic range and more living individuals than any other listed land animal, biologists have needed to detect population trends against a “noisy” background of strong annual changes. We obtained annual population estimates of desert tortoises over 6 consecutive years at a 2.59‐km 2 plot in Joshua Tree National Park, California. Our estimates, based on weekly spring surveys, varied substantially, particularly between wet and dry years. Concurrently, we followed 10 radiotagged animals for 3 years to corroborate the surveys. Population density was determined separately for each year and for all years combined. Our best population estimate was an average of 67 adult tortoises, three times more than the density reported in a 1978 survey of the same site. Annual mortality was low (

Unusual Behavior of Polygyne Fire Ant Queens on Nuptial Flights - Michael A. D. Goodisman; Christopher J. DeHeer; Kenneth G. Ross (Journal of Insect Behavior, 2000)

Effects of Exotic Lonicera and Rhamnus on Songbird Nest Predation - Kenneth A. Schmidt; Christopher J. Whelan (Conservation Biology, 1999)
Habitat fragmentation and disturbance exacerbate the invasion of exotic plant species that, in turn, may attract nesting songbirds by providing a branch structure suitable for nest sites. We document that American Robin ( Turdus migratorius ) nests in two exotic plants, Lonicera maackii and Rhamnus cathartica , experienced higher predation than nests built in comparable native shrubs ( Crataegus, Viburnum ) and native tree species. This was due to a combination of lower nest height, the absence of sharp thorns on the exotic species, and perhaps a branch architecture that facilitated predator movement among the exotic species. In a more subtle interaction, nesting Wood Thrushes ( Hylocichla mustelina ) experienced apparent competition with robins for nest sites in Lonicera , and this interaction was further aggravated by an increased selectivity for Lonicera by nesting robins, possibly due to their early leaf flush and expansion. By documenting increased nest predation in songbirds nesting in exotic shrubs, our results suggest that restoring native plant communities may benefit the surrounding avian community.

NBl-C16-Insulin: Site-Specific Synthesis, Purification, and Biological Activity - Hong Mei; X. Christopher Yu; Kenneth K. Chan (Pharmaceutical Research, 1999)

The 1882 tilefish kill — a cold event in shelf waters off the north‐eastern United States? - ROBERT MARSH; BRIAN PETRIE; CHRISTOPHER R. WEIDMAN; ROBERT R. DICKSON; JOHN W. LODER; CHARLES G. HANNAH; KENNETH FRANK; KEN DRINKWATER (Fisheries Oceanography, 1999)
A mass mortality of `warm‐water' tilefish in the Middle Atlantic Bight between April and August of 1882 suggests an episode of extreme cold in the shelf waters off the north‐eastern United States. This cooling is hypothesized to be a consequence of enhanced equatorwards transport of cold water in the Labrador Current, coincident with a minimum in the North Atlantic Oscillation (NAO) index during the early 1880s. Although there is little direct evidence for this historical event, an analogue for the 1880s cooling is found in the 1960s, at the most recent NAO‐index minimum. Post‐1945 observations in the Middle Atlantic Bight / Gulf of Maine region reveal changes in winter baroclinic circulation between cool and warm decades, with greater equatorward penetration of south‐westwards flow along the shelf‐edge during the cool 1960s. Over the period 1934–77, the NAO is found to account for 17% of the interannual variance in Labrador Current transport around the Grand Banks. Proxy evidence for the cold episode of the early 1880s is sought. Records of bottom temperature in the Middle Atlantic Bight region are reconstructed using stable oxygen isotopic analysis on the annual bands of shells of a bivalve mollusc ( Arctica islandica ) and an empirical model of covariability with local air temperature. The result is confirmation of the presence of anomalously cold water during the early 1880s.

The Relative Impacts of Nest Predation and Brood Parasitism on Seasonal Fecundity in Songbirds - Kenneth A. Schmidt; Christopher J. Whelan (Conservation Biology, 1999)
The impacts of nest predation and brood parasitism on the seasonal fecundity of birds are strongly dependent on the number of nesting attempts, and thus seasonal fecundity is responsive to behavioral traits that increase the number of opportunities to nest. We developed simple models to investigate the relative impacts of nest predation and brood parasitism on seasonal fecundity in songbirds. In particular, we asked to what extent songbirds can ameliorate the negative effects of high nest predation and brood parasitism often typical of fragmented, urbanized, and agricultural landscapes through (1) renesting following predation, (2) abandoning and renesting following parasitism, and (3) double brooding—renesting following a successful brood. Our model assigned probabilities to all possible fates of breeding females and calculated seasonal fecundity by summing up the individual probabilities. We analyzed the model through the use of fecundity isopleths, which allow one to visually determine the impact of predation and parasitism simultaneously over the entire range of probabilities. Our analysis indicates that (1) nest predation has a greater impact on seasonal fecundity over a larger range of parameter space than does parasitism, especially when brood loss due to parasitism is low; (2) songbird populations experiencing nest predation probabilities typical of fragmented landscapes (>0.65) are unlikely to be self‐sustaining; and (3) amelioration of nest predation through frequent renesting or double brooding may be insufficient to establish self‐sustaining populations. These results suggest that predator control should be at least as high a priority as parasitism control, particularly for species that suffer moderate to low brood reduction due to parasitism and that are single‐brooded. Programs aimed solely at managing cowbirds likely will be of limited success.

Conservation of Pacific Salmon: Response to Wainwright and Waples - Kenneth P. Currens; Fred W. Allendorf; David Bayles; Daniel L. Bottom; Christopher A. Frissell; David Hankin; James A. Lichatowich; Patrick C. Trotter; Thomas A. Williams (Conservation Biology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Prioritizing Pacific Salmon Stocks for Conservation - Fred W. Allendorf; David Bayles; Daniel L. Bottom; Kenneth P. Currens; Christopher A. Frissell; David Hankin; James A. Lichatowich; Willa Nehlsen; Patrick C. Trotter; Thomas H. Williams (Conservation Biology, 1997)
Over 300 native stocks of Pacific salmon, steelhead, and coastal cutthroat trout (Oncorhynchus spp.) are at risk of extinction in the Pacific Northwest. With only limited resources available for conservation and recovery, prioritization of these stocks may become necessary if meaningful measures are to be implemented. We propose criteria by which prioritization may be guided. First, we rank stocks for risk of extinction, either by population viability analysis or by a set of surrogate measures. Then we rank stocks for biological consequences of extinction, using sets of questions designed to establish the genetic and evolutionary consequences and the ecological consequences if a stock were to become extinct. Together, these rankings allow stocks to be prioritized for a range of possible actions, with those stocks at highest risk and bearing the greatest biological consequences of extinction receiving attention first. Application of the prioritization process to 20 Pacific anadromous salmonid stocks worked as intended, although data limitations are considerable. The process is most likely to work successfully when applied to many stocks on which data exist, when several experts carry out the prioritization, and when the results are peer reviewed.

Lack of detectable nepotism in multiple-queen colonies of the fire ant Solenopsis invicta (Hymenoptera: Formicidae) - Christopher J. DeHeer; Kenneth G. Ross (Behavioral Ecology and Sociobiology, 1997)

Fundamental patterns of bilateral muscle activity in human locomotion - Kenneth S. Olree; Christopher L. Vaughan (Biological Cybernetics, 1995)

Fundamental patterns of bilateral muscle activity in human locomotion - Kenneth S. Olree; Christopher L. Vaughan (Biological Cybernetics, 1995)